Importance of Intuition in Music Education - Kirliauskienė, Rasa (Pedagogika, 2014)
Communication of music is firstly based on intuitive intonational thinking. Thus, according to Z. Rinkevičius (2009), it is quite natural that appropriate use of music may efficiently stimulate intuitive thinking, reserves of unknown to us subconsciousness, and through them, those of consciousness. Therefore, music facilitates improvement of spiritual powers and intellect more than any other kinds of art. Research object: importance of intuition in music education. Research aim: to reveal importance of intuition in music education. Methods of research and sample: analysis of scientific literature sources, interview. Qualitative research data are described applying content analysis. The scheme of categorization was not planned in advance and it was devised on the basis of the received data. The research was carried out in October 2013 and January 2014. The people related to the analysed problem (key informants) were chosen in the first stage of the research: 3 teachers with sufficient pedagogical experience working at school. The semi-structured (oral) interview was employed. The focus of this stage of research was on subjective opinion of the informants about importance of intuition in music education. They also were asked in what way, according to the informants, intuition is manifested in their work as a phenomenon. Attempts were also made to identify the musical activities, where use of intuition is evidenced. The second stage of the research included 28 fourth year (full-time and part-time) students. The semi-structured interview (written) was used in this stage. The question about importance of intuition in musical education was not presented to future teachers of music with the acquired sufficient knowledge of pedagogy, psychology and other theories, speciality - related abilities and skills of observational and performance practices. They were asked to express their opinion about the content of the role of a contemporary music teacher. The question about significance of intonation was not presented to the informants making attempts to envisage the vision of the young generation (i.e., music teachers to be) about what a school teacher should be like and then the researcher searched for certain links to substantiate own theory. Conclusions • The research revealed that music teachers frequently act under influence of intuition, change plans when new ideas emerge and get overwhelmed with an impulse of creativity. According to them, manifestations of intuition in music activities are mostly expressed in music creation, listening to music, music playing and musical thinking. • The research data identified the content of the role of a music teacher pointing out its 5 aspects: educator (education for humanity: humanity, communication, playing music together); authority (competent specialist: example for school learners, profound knowledge of study subject, universality); importance of teacher’s personality (aspects of teacher’s personality: ability to arouse learners’ interest, ability to be a friend, teacher’s charismatic personality, flexibility); creativity (manifestations of creativity: teacher’s creativity, ability to develop students’ creativity, improvisation, revelation of students’ personality through creative expression) and value-based aspects (enlightener of students’ souls, nurturer of beauty of life, provision of sense to new impressions, expression of emotions). • The content of the role of a contemporary music teacher revealed during the research substantiates possibilities of intuition in music education and expands its boundaries.